2016
DOI: 10.1021/acs.inorgchem.5b02990
|View full text |Cite
|
Sign up to set email alerts
|

Oxidatively Triggered Carbon–Carbon Bond Formation in Ene-amide Complexes

Abstract: Ene-amides have been explored as ligands and substrates for oxidative coupling. Treatment of CrCl2, Cl2Fe(PMe3)2, and Cl2Copy4 with 2 equiv of {(2,6-(i)Pr2C6H3)(1-(c)Hexenyl)N}Li afforded pseudosquare planar {η(3)-C,C,N-(2,6-(i)Pr2C6H3)(1-(c)Hexenyl)N}2Cr (1-Cr, 78%), trigonal {(2,6-(i)Pr2C6H3)(1-(c)Hexenyl)N}2Fe(PMe3) (2-Fe, 80%), and tetrahedral {(2,6-(i)Pr2C6H3)(1-(c)Hexenyl)N}2Co(py)2 (3-Co, 91%) in very good yields. The addition of CrCl3 to 1-Cr, and FeCl3 to 2-Fe, afforded oxidatively triggered C-C bond … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 111 publications
0
10
0
Order By: Relevance
“…Interestigly, the Woclzansy group has reported recently that C-C couplingmediated by aza-enolate (iminate) complexes also requires oxidation of the metal center. 20 Scheme 3. Exchange reaction of (4-allyl-Mes HBIP)2 with Zn and Pd alkyls.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestigly, the Woclzansy group has reported recently that C-C couplingmediated by aza-enolate (iminate) complexes also requires oxidation of the metal center. 20 Scheme 3. Exchange reaction of (4-allyl-Mes HBIP)2 with Zn and Pd alkyls.…”
Section: Resultsmentioning
confidence: 99%
“…The need for an external trigger to switch the reaction outcome indicates that intermediate Mn­(II) dihydropyridinate complexes 1 are themselves unable to undergo dimerization but become activated when they react with oxygen. Interestigly, the Woclzansy group has reported recently that C–C coupling mediated by aza-enolate (iminate) complexes also requires oxidation of the metal center …”
Section: Resultsmentioning
confidence: 99%
“…Carbon–carbon bond formation is often a consequence of redox noninnocence (RNI) that induces radical character in certain ligands. In many cases, a relatively simple coupling of carbon radicals occurs to form a single new bond, but sometimes the reactivity can be complicated. Figure illustrates some unusual C–C bond forming events discovered in these laboratories. In A , the Ti­(III) complex, (smif)­{Li­(smif–smif)}­Ti, was shown to contain one C–C bond derived from coupling of smif (smif = 1,3-di­(2-pyridyl)-2-azaallyl) ligands that were reduced during the course of its synthesis. One mode of its decomposition generated dimer [(smif 2– )­Ti III ] 2 (μ-κ 3 ,κ 3 - N , N (py) 2 -smif,smif), which contained two new C–C bonds that can be construed as arising from coupling of a singlet diradical, or alternatively, a nucleophile/electrophile coupling .…”
Section: Introductionmentioning
confidence: 98%
“…The formation of a cyclopropanated backbone of (dadi) n suggested that reversible C–C bond formation could be a means of storing and releasing electrons in a redox noninnocent (RNI) fashion. , A possible hindrance to RNI is the transfer of a cyclopropane hydrogen subsequent to ring-opening, which would generate a nacnac fragment in place of the original diimine. The reactivity of {PhC 3 H 3 (-NC 6 H 4 -2-NAr) 2 }­Ti­(THF) ( 3 ) was probed via various potential oxidants and proton acceptors, and while most generated mixtures, the addition of Ph 2 CN 2 yielded a single product (>90%) that was dissymmetric.…”
Section: Resultsmentioning
confidence: 99%